APPLICATION OF BANANA BASED AGRO-WASTE AS A PRECURSOR OF HETEROGENEOUS CATALYST FOR BIODIESEL PRODUCTION - VISWANATHAN, Santhosh; PERIYASAMY, Siva; KANDASAMY, Senthilkumar (Studia Universitatis Babeș-Bolyai Chemia, 2025)
In the recent decades, the exploration of agro-wastes and other renewable biomass wastes as a precursor of heterogeneous catalysts for transesterification has become more fascinating in contrast to the conventional homogeneous catalysts. This is mainly attributed by its peculiar characteristics such as easy separation, reusability, cost effectiveness, eco friendliness, etc. Hence, the potential of banana inflorescence (BI), a byproduct of banana cultivation with less economic value was investigated herein, for the development of a competent heterogeneous catalyst for profitable biodiesel production from Used cooking oil (UCO). The transformation in porosity, surface area and chemical composition of banana inflorescence, brought about by calcination was examined by Scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET), Powder X-ray diffractogram (XRD), Fourier transform infrared spectroscopy (FTIR) and Energy Dispersive X-ray Spectroscopy (EDS) analysis. The conversion was enumerated by Nuclear magnetic resonance (1H NMR) spectroscopy and it was observed that transesterification using 2 wt% catalyst, 9:1 methanol to oil molar ratio for a reaction time of 75 min at 65 ºC showed a fatty acid methyl ester (FAME) conversion of 98.62%.